THE RELEVANCE OF JAMAL AL-BANNA ISLAMIC LEGAL THOUGHT IN RELIGIOUS MODERATION - Amrar Mahfuzh Faza; Asmuni Asmuni; Zainul Fuad (Jurnal Pembaharuan Hukum, 2023)
This research examines the principles of Islamic legal thought of Jamal al-Banna with the aim of knowing the relevance of the principles of Islamic legal thought to the principles of religious moderation in Indonesia. The purpose of this research is to analyze the Intellectual Biography of Jamal al-Banna and the Principles of Islamic Legal Thought of Jamal al-Banna Relevant to the Principles of Religious Moderation in Indonesia. This research is a doctrinal Islamic law research using historical (historical) content analysis approach. The primary data source for this research is the work of Jamal al-Banna himself namely Naá¸¥wa Fiqh JadÃ®d and the book Religious moderation authored by Research and Development Team of the Ministry of Religion of the Republic of Indonesia.This research is also supported by secondary sources in the form of works related to the topic of study. Religious moderation is actually the essence and substance of religious teachings which are not exaggerated at all, either in perspective or attitude. This study concludes There are 2 (two) textually the principles of Islamic legal thought of Jamal al-Banna that are relevant to religious moderation in Indonesia, namely: justice and tolerance. As for substantially there are also 2 (two), namely: the value of the principle of "facilitating" is the same as Tawassut and compassion is the same as the principle of equality (musawah/egalitarian).